THE LIQUIDITY AND INFORMATIONAL EFFICIENCY IN STOCK AND BOND MARKET - Dewi Tamara (Jurnal Keuangan dan Perbankan, 2011)
This paper was taking a first step toward an integrated approach to stock and bond liquidity and informationalefficiency. We drew from the literature to develop comprehensive understanding about liquidity and informationevent in stock and bonds market. We used variables from Chordia, et al. (2005), to explore cross-marketliquidity dynamics by estimating a vector regressive model for liquidity such as bid-ask spread and depth,returns, volatility, and order flow in the stock and Treasury bond markets. We analyzed the work fromHotchkiss, et al. (2002) to find the informational efficiency of corporate bond prices. It was similar to that of theunderlying stocks. The central contribution of this paper was to reveal the possibility in applying this kind ofresearch in Indonesian market.